2014
DOI: 10.1111/jfq.12076
|View full text |Cite
|
Sign up to set email alerts
|

Ghost Structures, Pasting, Rheological and Textural Properties between Mesona Blumes Gum and Various Starches

Abstract: In this study, the ghost structures of potato starch granule gelatinization in the presence and absence of Mesona Blumes gum (MBG) at different temperatures and time points were studied. Our results indicated that ghost structures could form merely after the amylose was completely leached from granules. In addition, MBG could prevent amylose from leaching outside the granules, and thus extend ghost structure existence in aqueous solution. Furthermore, the interactions among eight kinds of starches and MBG were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 30 publications
(54 reference statements)
0
8
0
Order By: Relevance
“…In particular, it was demonstrated that soluble dietary fiber (SDF) displayed stronger antioxidant activity than insoluble dietary fiber (IDF) (Esposito et al, 2005). In addition, compared to IDF, SDF has a higher capacity to form gels and act as an emulsifier, enabling it to be readily incorporated into food products (Feng et al, 2013(Feng et al, , 2014Jenkins et al, 2006;Mateos-Aparicio, Mateos-Peinado, & RupĂ©rez, 2010;Sozer, Cicerelli, Heiniö, & Poutanen, 2014). There is increasing evidence that the structural features and molecular weight of polysaccharides are of fundamental importance since they are highly associated with the physicochemical and functional properties of polysaccharides.…”
Section: Introductionmentioning
confidence: 98%
“…In particular, it was demonstrated that soluble dietary fiber (SDF) displayed stronger antioxidant activity than insoluble dietary fiber (IDF) (Esposito et al, 2005). In addition, compared to IDF, SDF has a higher capacity to form gels and act as an emulsifier, enabling it to be readily incorporated into food products (Feng et al, 2013(Feng et al, , 2014Jenkins et al, 2006;Mateos-Aparicio, Mateos-Peinado, & RupĂ©rez, 2010;Sozer, Cicerelli, Heiniö, & Poutanen, 2014). There is increasing evidence that the structural features and molecular weight of polysaccharides are of fundamental importance since they are highly associated with the physicochemical and functional properties of polysaccharides.…”
Section: Introductionmentioning
confidence: 98%
“…Although the bioactivity of SDF is inferior to vitamins or mineral components, they have unique properties with diverse physiological and metabolic roles in human organisms (Nawirska and Kwaƛniewska 2005), and also can adsorb and remove toxic heavy metals (Ou et al 1999). Moreover, compared with IDF, SDF has excellent water holding capacity and viscosity, enabling it to be readily fermented by microflora in the intestine and incorporated into other food products (Feng et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…DF could be classified into insoluble (IDF) and soluble dietary fiber (SDF) based on whether it could form a dispersion or not when mixed with water (JimĂ©nez-Escrig & SĂĄnchez-Muniz, 2000). Compared to IDF, SDF had certain better physiological and bioactive properties, such as stronger antioxidant activity, higher capacity to form gels, greater fermentability and viscosity (Esposito et al, 2005; Mateos-Aparicio, Mateos-Peinado, & RupĂ©rez, 2010;Feng et al, 2014;Galisteo, Duarte, & Zarzuelo, 2008). Thus SDF could be readily applied to food products as thickeners, emulsifiers, stabilisers, and fat replacers (Cui, Wu, & Ding, 2013;Sozer, Cicerelli, Heiniö, & Poutanen, 2014).…”
Section: Introductionmentioning
confidence: 99%